KAJIAN PENGARUH CHITOSAN TERHADAP PROFILLIPOPROTEIN, FUNGSI ENDOTELIAL AORTA DAN ARTERIA KORONARIA TIKUS PUTIH SPRAGUE DAWLEY DIINDUKSI LEMAK TINGGI - , SRI ISDADIYANTO,SSi, MSi; , Prof. Sukarti Moeljopawiro, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Atherosclerosis, the most common cause of death in developing country is a complex process involving the interplay of genetic and environmental factors and the involvement of multiple cell types. Injury to the vascular endothelium is thought to iniate the atherosclerotic lesion. The objective of this study was to analyze the influences of chitosan on lipoprotein profile, endothelial function of aorta, endothelial function of coronary artery, and C-Reactive Protein in rats by high fat induction. Twenty male Sprague Dawley rats, 1,5 months of age were used as experimental animals. All rats were adapted in 20 single cages for 7 days and given basal diet containing normal fat and water ad libitum. The rats were divided into 4 groups of 5. Group I was fed basal diet containing normal fat for 3 months. Group II, III and IV was fed high fat diet. Group II was used as a control (no treatment). Group III was fed chitosan 180 mg kg BW per day. Group IV was given chitosan using the same doses as group III, one month after feeding high fat diet. Chitosan was given orally in 2 ml aquadest. After 90 days, each rat was fast for 12-14 hours before blood collected. Blood was collected from the orbital vein for lipoprotein profile analysis. The rats were then sacrificed and the heart including aorta were collected for histopathological and immunohistochemical (expression of CRP) analysis. The difference between treatment was statistically analyze by Anava, and continued by LSDT to locate the difference. The result showed that high fat diet decreased HDL level, apoprotein A concentration, endothelial function of aorta and coronary artery, but increased total cholesterol level, LDL level and apoprotein B concentration. Chitosan increased HDL level and apoprotein A concentration, but decreased total cholesterol level, LDL level and apoprotein B concentration in rats by high fat induction. High fat diet increased coronary artery wall thickness and chitosan could be decreased coronary artery in rats. High fat diet + chitosan that given simultaneously could be increased coronary artery lumen diameter in rats. All those results were statistically significant (P<0,05). High fat diet did not significantly decreased coronary artery lumen diameter, as well as the rats that given chitosan after one month. Histopatologic analysis of aorta and coronary artery of rats that given normal diet showed that there was no atherosclerotic lesions, whereas aorta in rats fed high fat diet (P1) showed atheroma plaques. Structural illustration of aorta and coronary artery in rats fed high fat diet + chitosan (P2) did not show atherosclerotic lesions, whereas the group of rats that given chitosan after 1 month (P3), also did not show atherosclerotic lesions, in spite of several of aortas were atheroma plaques illustration. Immunohistochemistry analysis using antibody anti CRP of aortas showed that expression of CRP negative for all groups. CRP expression of coronary artery of rats that given normal diet (K) were negative, whereas rats that given high fat diet (P1) and no treatment were positive. CRP expression of coronary artery for rats that given high fat diet and given chitosan (P2) were negative, but rats that given chitosan after one month (P3) were positive. The overall results can be said that: 1. High fat diet decreased HDL level, apoprotein A concentration, endothelial function of aorta and coronary artery